Ru(II)- and Ir(I) Catalyzed Hydrogen Peroxide Oxidation of Hydroxamic Acids and their Subsequent Hetero Diels-Alder Cycloadditions with Chiral N-Dienyl Lactams - Fakhruddin, Ahmad; Phomkeona, Kesiny; Abu-Elfotoh, Abdel-Moneim; Shibatomi, Kazutaka; Iwasa, Seiji (Letters in Organic Chemistry, 2010)
Asymmetric hetero Diels-Alder (HDA) reaction of highly reactive acyl nitroso intermediates are reported. Transient acyl nitroso compounds 2a'-c' are formed by Ru(II)- or Ir(I)-catalyzed hydrogen peroxide oxidation of hydroxamic acids 2a-c and are trapped in situ by the optically pure N-dienyl-L-pyroglutamates 1a-b to afford the corresponding diastereomeric adducts 3a-f and 4a-f up to 98% yield (70% de) and 72% de (70% yield) with complete regioselectivity at 0°C to room temperature.
Keywords: 1; 2-oxazine